Civil Responsibility Resulting from Clinical Trials According to UAE Ministerial Resolution No. (730) for (2018) - Emad , Hadeer; Jad Al-Haq, Iyad (Journal of Legal Sciences, 2023)
This study includes the new methods especially those related to clinical trials non-therapeutic clinical trials and new risks that may be exposed to. The Corna pandemic has raised many repercussions on all levels and fields, and raised many questions, especially in the legal field. Where many responsibilities arise because of the way to deal with this pandemic, exploit it, or neglect some of the obligations imposed to confront this pandemic. Therefore, the legislator had to intervene to organize practice of such clinical trials in order to ensure stability and reassurance, whether to the doctor, researcher or people who subject to such clinical trial in accordance with the Ministerial Resolution No. (730) of (2018). Therefore, such trials had to be discussed, especially such trails are still of concern because they focus on human body the thing that may cause damage to the person, who subject to such clinical trial, who, in turn, should ensure such damage, Therefore, it was necessary to clarify civil liability as it is an important part in the scope of treating the effects resulting from clinical trials, as some people deliberately or negligently tend to harm others, which calls for recourse to the provisions of civil liability, and that the burden of civil liability does not fall on individuals only, but may affect individuals morale as well. This study is in the field of scientific technology and medicine that affects the person and his body, whether during his life or after his death, to achieve the various goals of these experiments through using it as a laboratory method.